2013
DOI: 10.13005/ojc/290242
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption Equilibrium Isotherms Freundlich, Langmuir, and Temkin Models for Two Steroidal anti-Inflammatory Drugs (NSAIDs) Betamethasone and Clobetasol on Multi-Walled Carbon Nanotube

Abstract: We have studied the interaction of Betamethasone and Clobetasol solutions on multi carbon nanotube. After investigated comparative study and assigned to either Betamethasone or Clobetasolon adsorption isotherms. The adsorption equilibrium isotherms were fitted by Freundlich, Langmuir, and Temkin models. It was found that the Langmuir model described the adsorption process better than other two isotherm models. The amount of SAIDs (Betamethasone, Clobetasol) adsorbed on carbon nanotube surface increased with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Similar studies conducted on carbon nanotubes and lipophilic drugs such as betamethasone showed "n" and "k" values of 0.7 and 5.1 mg g-1, respectively. This could be explained by the large surface area and hydrophobic character of the carbon nanotubes [27]. On the other hand, CAC and CAM presented a good fit to the Elovich model, which describes that the adsorption increases exponentially with the available multilayer adsorption sites [28].…”
Section: Fig 3: N2 Isotherms Of the Adsorbentsmentioning
confidence: 95%
“…Similar studies conducted on carbon nanotubes and lipophilic drugs such as betamethasone showed "n" and "k" values of 0.7 and 5.1 mg g-1, respectively. This could be explained by the large surface area and hydrophobic character of the carbon nanotubes [27]. On the other hand, CAC and CAM presented a good fit to the Elovich model, which describes that the adsorption increases exponentially with the available multilayer adsorption sites [28].…”
Section: Fig 3: N2 Isotherms Of the Adsorbentsmentioning
confidence: 95%